Mechanical behaviour of fire damaged steel fibre reinforced concrete (SFRC) - Norlila, Omar (2017)
Since past few decades ago, there has been a rapid advancement in concrete technology where it is focused on the improvement in concrete strength and other structural properties. Therefore, the development of concrete in the form of steel fibre reinforced concrete has been discovered in fulfill the main purpose on improving the concrete properties and concrete behavior and also as an alternative to provide more economical options to be practice in construction field. This study represents a research on mechanical behaviour of steel fibre reinforced concrete specimens which has been imposed to a certain temperature. In this research, there are three method of experimentation selected to find out the effect of temperature in determining the compressive strength, flexural strength and also tensile strength on steel fibre reinforced concrete specimens.